Bullying Victimization as a Strain: Examining Changes in Bullying Victimization and Delinquency among Korean Students from a Developmental General Strain Theory Perspective. (February 2020) - Park, Yeoju; Metcalfe, Christi
Objectives: Using a developmental extension of Agnew's general strain theory (GST), the current study aims to assess the within-individual associations between bullying victimization and delinquency, as well as the recent versus enduring effects of bullying victimization experiences and the moderating influences of several risk factors. Method: Random effects Tobit models are conducted to examine the relationship between changes in bullying victimization and five forms of delinquency using five waves from the Korean Youth Panel Survey. A measure calculating the duration of consecutive bullying experiences is introduced into these models to capture the enduring effects of this strain, and margins analyses are used to assess moderating influences. Results: There is a positive relationship between experiencing a bullying event and delinquency, and this relationship is stronger at higher levels of risk factors. Moreover, bullying victimization over consecutive years has a consistent harmful effect with regard to analogous behavior and violence and theft, as opposed to a diminishing effect for overall delinquency, substance use, and bullying. Conclusions: While there is support for many of the propositions of GST, there are some inconsistences regarding the duration effects. The findings suggest the need for further assessments of the temporal patterns of strains.